Effect of Acid Activation-Hydrophilic-Modified Sepiolite on Comprehensive Properties of Oil-Well Cement - Yihang Zhang; Miao He; Mingbiao Xu; Peng Xu (Journal of Chemistry)
In this paper, sepiolite was treated by acid activation, coupling agent treatment, and sulfonation modification. The purpose of this study was to explore the changes in the fluidity and mechanical properties of sepiolite cement slurry before and after modification. Therefore, the comprehensive properties of unmodified sepiolite fiber (HPS) and acid activation-coupling agent treatment-sulfonated sepiolite fiber (S-O-H-HPS) in oil-well cement slurry were evaluated. FT-IR and microscopic mechanism of cement paste fracture surface before and after sepiolite modification were analyzed. The results showed that HPS can effectively improve the toughness of cement paste, but when the content of HPS was more than 1%, the fluidity of cement paste deteriorated sharply and the compressive strength decreased gradually. The addition of S-O-H-HPS can significantly improve the fluidity and stability of HPS slurry. Without affecting the compressive strength, it can effectively improve the flexural strength and impact strength and reduce the elastic modulus of cement paste. The mechanism analysis showed that S-O-H-HPS can not only form network structure in cement paste but also improve the toughness of cement paste by forming a bridge. This also explains why the strength of S-O-H-HPS cement paste does not decrease significantly with the increase of S-O-H-HPS.